Paper strength enhancer and paper

By mixing metal inorganic acid salt with (meth)acrylamide-based polymer to form a paper force enhancer, the problem of reducing the fixing effect of aluminum sulfate in the prior art is solved, and an efficient paper force enhancement effect is achieved while reducing environmental load.

CN119895097APending Publication Date: 2025-04-25ARAKAWA CHEM IND LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380060724.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-06
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the closed environment of the papermaking system, the fixed effect of aluminum sulfate is reduced, resulting in insufficient paper force effect and increased environmental load.

Method used

By mixing a specific metal inorganic acid salt with a (meth)acrylamide-based polymer, a paper force enhancer is formed to improve the viscosity and paper force effect of the paper.

Benefits of technology

It is achieved that the paper force effect of significantly improving the paper while reducing the amount of aluminum sulfate addition is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005277292180000131
    Figure BDA0005277292180000131
  • Figure BDA0005277292180000141
    Figure BDA0005277292180000141
  • Figure BDA0005277292180000171
    Figure BDA0005277292180000171
Patent Text Reader

Abstract

The present invention relates to a paper strength enhancer and paper comprising the same, the paper strength enhancer comprising a mixture of a (meth) acrylamide polymer (A) and a metal inorganic acid salt (B), the (meth) acrylamide polymer (A) contains (meth) acrylamide (a1), a polymerizable monomer (a2) having an amino group, and a polymerizable monomer (a3) having a carboxyl group as essential components, and the metal inorganic acid salt (B) has a divalent or trivalent metal atom having an atomic weight of 30-80. The paper strength enhancer shows an excellent paper strength effect when being made into paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a paper strength enhancer and paper. Prior art

[0002] Paper strength agents are chemicals used to increase the strength of paper itself. In particular, in the papermaking industry, as the papermaking system becomes more closed (such as the recycling of waste paper pulp), the strength of the paper obtained is further reduced due to the reduction in the strength of the pulp fiber as the raw material. In this environment, the importance of paper strength agents continues to increase.

[0003] Furthermore, as a paper strengthening agent, general (meth)acrylamide polymers are classified into anionic, cationic and amphoteric types according to their ionicity. Among them, the mainstream amphoteric (meth)acrylamide polymers are obtained by copolymerizing a polymerizable monomer such as a cationic monomer or anionic monomer with acrylamide (Patent Document 1).

[0004] When the above polymer is added to the pulp slurry of the papermaking system, aluminum sulfate is added as a fixing agent before or after the addition of the polymer. However, as the papermaking system is closed, the fixing effect of aluminum sulfate decreases. In addition, from the perspective of environmental load, there is also a behavior of reducing the amount of aluminum sulfate added in papermaking factories, and the paper strength effect of the paper strengthener itself is difficult to further exert, which becomes a problem. As a solution, it has been known that a paper strengthener prepared by pre-mixing a (meth)acrylamide polymer with a water-soluble aluminum compound such as aluminum sulfate is added to the pulp slurry (Patent Document 2, Patent Document 3). Although this mixed paper strengthener has advantages in, for example, reducing the amount of aluminum sulfate added to the pulp slurry and improving the paper strength effect, its effect is not sufficient. Prior art literature

[0005] Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2012-251252 Patent Document 2: Japanese Patent Application Publication No. 2001-011787 Patent Document 3: Japanese Patent Laid-Open No. 8-226092 Summary of the invention Technical problem to be solved by the invention

[0006] The technical problem of the present invention is to provide a paper strength enhancing agent having excellent paper strength effect. Technical means to solve technical problems

[0007] The present inventors have conducted intensive studies and have found that the above-mentioned technical problems can be solved by blending a specific metal inorganic acid salt into a (meth)acrylamide polymer, thereby completing the present invention. That is, the present invention relates to the following paper strengthening agent and paper.

[0008] 1. A paper strengthening agent, comprising a mixture of a (meth)acrylamide polymer (A) and a metal inorganic acid salt (B), wherein the (meth)acrylamide polymer (A) contains (meth)acrylamide (a1), a polymerizable monomer having an amino group (a2) and a polymerizable monomer having a carboxyl group (a3) ​​as essential components, and the metal inorganic acid salt (B) contains a divalent or trivalent metal atom having an atomic weight of 30 to 80.

[0009] 2. The paper strengthening agent according to item 1 above, wherein the mixture has a viscosity of 5 mPa·s or more and 5000 mPa·s or less at a temperature of 25° C. when the mixture is prepared as an aqueous solution of pH 6 containing 1% by weight of the component (A) as a nonvolatile matter concentration.

[0010] 3. The paper strengthening agent according to the above item 1 or 2, wherein the constituent components further include a polymerizable monomer (a4) having a sulfonic acid group and / or a polymerizable monomer (a5) having a crosslinkable group.

[0011] 4. The paper strengthening agent according to item 1 or 2 above, wherein the component (B) is at least one selected from the group consisting of titanium chloride, titanium sulfate, titanium phosphate, ferric nitrate, ferric chloride, polyferric chloride, ferric sulfate, polyferric sulfate, ferric phosphate, polyferric phosphate, ferric silicate and polyferric silicate.

[0012] 5. The paper strengthening agent according to the above item 1 or 2, wherein the mixture further comprises a water-soluble aluminum compound (C).

[0013] 6. A paper comprising the paper strengthening agent as described in 1 or 2 above. Beneficial Effects

[0014] The paper strength enhancer according to the present invention exhibits excellent paper strength effect when made into paper. DETAILED DESCRIPTION

[0015] The paper strengthening agent of the present invention comprises a mixture of a (meth)acrylamide polymer (A) (hereinafter referred to as component (A)) and a metal inorganic acid salt (B) (hereinafter referred to as component (B)), wherein the (meth)acrylamide polymer (A) comprises (meth)acrylamide (a1) (hereinafter referred to as component (a1)), a polymerizable monomer (a2) having an amino group (hereinafter referred to as component (a2)) and a polymerizable monomer (a3) ​​having a carboxyl group (hereinafter referred to as component (a3)), and the metal inorganic acid salt (B) has a divalent or trivalent metal atom having an atomic weight of 30 to 80.

[0016] The component (a1) is methacrylamide or acrylamide, and these may be used alone or in combination of two.

[0017] The molar ratio of the component (a1) is preferably 50 mol % to 99.45 mol %, more preferably 61 mol % to 98.88 mol %, and even more preferably 68 mol % to 97.48 mol %, based on 100 mol % of all the constituents.

[0018] (a2) component is a polymerizable monomer having an amino group. As (a2) component, for example, there can be listed: a polymerizable monomer having a primary amino group, a polymerizable monomer having a secondary amino group, a polymerizable monomer having a tertiary amino group, and quaternary ammonium salts of these polymerizable monomers. These can be used alone or in combination of two or more.

[0019] Examples of the polymerizable monomer having a primary amino group include vinylamine and allylamine, which may be used alone or in combination of two or more.

[0020] Examples of the polymerizable monomer having a secondary amino group include diallylamine, etc. These may be used alone or in combination of two or more.

[0021] Examples of polymerizable monomers having a tertiary amino group include (meth)acrylates having a tertiary amino group such as N,N-dimethylaminoethyl (meth)acrylate and N,N-diethylaminoethyl (meth)acrylate; (meth)acrylamides having a tertiary amino group such as N,N-dimethylaminopropyl (meth)acrylamide and N,N-diethylaminopropyl (meth)acrylamide, etc. These monomers may be used alone or in combination of two or more.

[0022] The quaternary ammonium salt of these monomers refers to the salt formed by reacting the polymerizable monomer with primary amino group, the polymerizable monomer with secondary amino group or the polymerizable monomer with tertiary amino group with quaternizing agent, etc. As quaternary ammonium salt, it can be inorganic acid salts such as hydrochloride and sulfate, and it can also be organic acid salts such as acetate. In addition, as quaternizing agent, methyl chloride, benzyl chloride, dimethyl sulfate, epichlorohydrin, etc. can be listed. They can be used alone or in combination of two or more.

[0023] Among these (a2) components, it is preferred to contain a (meth)acrylate having a tertiary amino group and / or a quaternary ammonium salt of the (meth)acrylate. In addition, "(meth)acrylate" means methacrylate or acrylate (hereinafter the same).

[0024] The molar ratio of the component (a2) is preferably 0.5 to 20 mol %, more preferably 1 to 18 mol %, and even more preferably 2 to 16 mol %, based on 100 mol % of all the constituents.

[0025] Component (a3) ​​is a polymerizable monomer having a carboxyl group. Component (a3) ​​includes, for example: (meth)acrylic acid, acrylic anhydride, 2-(meth)acrylamide-N-glycolic acid, N-(meth)acryloyl glycine, 3-(meth)acrylamide propionic acid, 4-(meth)acrylamide butyric acid, itaconic acid, itaconic anhydride, fumaric acid, maleic acid, maleic anhydride, etc. In addition, these (a3) ​​components can also be used in the form of the following salts: alkali metal salts such as sodium and potassium; ammonium salts of ammonia; organic amine salts such as trimethylamine, triethylamine, trimethanolamine, triethanolamine, etc. They can be used alone or in combination of two or more. Among them, (meth)acrylic acid, acrylic anhydride, 2-(meth)acrylamide-N-glycolic acid, and itaconic acid are preferred.

[0026] The molar ratio of the component (a3) ​​is preferably 0.05 to 20 mol %, more preferably 0.1 to 15 mol %, and even more preferably 0.5 to 12 mol %, based on 100 mol % of all the constituents.

[0027] The above-mentioned components may further contain a polymerizable monomer (a4) having a sulfonic acid group (hereinafter also referred to as component (a4)).

[0028] (a4) component is a polymerizable monomer having a sulfonic acid group. Examples of (a4) component include vinyl sulfonic acid, methallyl sulfonic acid, p-styrene sulfonic acid, etc. In addition, these (a4) components can also be used in the form of alkali metal salts such as sodium and potassium or ammonium salts. They can be used alone or in combination of two or more.

[0029] The molar ratio of the component (a4) is preferably 5 mol% or less, more preferably 0.01 mol% to 3 mol%, and even more preferably 0.01 mol% to 2 mol%, based on 100 mol% of all the constituents.

[0030] The above-mentioned components may further contain a polymerizable monomer (a5) having a crosslinkable group (hereinafter also referred to as component (a5)).

[0031] Examples of the component (a5) include: N-alkyl (meth)acrylamide such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N-tert-butyl (meth)acrylamide; N,N-dialkyl (meth)acrylamide such as N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and N,N-diisopropyl (meth)acrylamide; N,N'-methylenebis(meth)acrylamide; N,N'-alkylenebis(meth)acrylamide, such as (meth)acrylamide, N,N'-ethylenebis(meth)acrylamide; crosslinking monomers having triallyl groups, such as triallyl isocyanurate, triallyl trimellitate, triallylamine, triallyl(meth)acrylamide; triazines having (meth)acryl groups, such as 1,3,5-triacryloyl-1,3,5-triazine, 1,3,5-triacryloylhexahydro-1,3,5-triazine, etc. They can be used alone or in combination of two or more. Among them, N,N-dimethyl(meth)acrylamide and N,N'-methylenebis(meth)acrylamide are preferably included.

[0032] The molar ratio of the component (a5) is preferably 5 mol% or less, more preferably 0.01 mol% to 3 mol%, and even more preferably 0.01 mol% to 2 mol%, based on 100 mol% of all the constituents.

[0033] As the above-mentioned constituent components, a monomer (a6) (hereinafter referred to as component (a6)) other than the components (a1) to (a5) may be further contained.

[0034] As the (a6) component, for example, there can be listed: polymerizable monomers having aromatic rings such as styrene, α-methylstyrene, and vinyltoluene; (meth) alkyl acrylates such as methyl (meth) acrylate, ethyl (meth) acrylate, n-propyl (meth) acrylate, n-butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, and cyclohexyl (meth) acrylate; vinyl carboxylates such as vinyl acetate and vinyl propionate; nitriles such as acrylonitrile; thiols such as 2-mercaptoethanol and n-dodecyl mercaptan; alcohols such as ethanol, isopropanol, and n-pentanol; aromatic compounds such as α-methylstyrene dimer, ethylbenzene, isopropylbenzene, and cumene; carbon tetrachloride, etc. These can be used alone or in combination of two or more. In addition, the molar ratio of the component (a6) is preferably 10 mol% or less, more preferably 8 mol% or less, and further preferably 5 mol% or less, with all the constituent components being 100 mol%.

[0035] In the production of the (meth)acrylamide polymer, organic acids such as acetic acid, propionic acid, butyric acid, citric acid, succinic acid, oxalic acid, glycolic acid, glyoxylic acid, etc.; inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, etc.; inorganic acid salts such as sodium sulfate, potassium sulfate, ammonium sulfate, etc. that do not belong to the component (B) described later; inorganic bases such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc.; starches such as oxidized starch, phosphated starch, urea-phosphated starch, etherified starch, cross-linked starch, APS-modified starch, enzyme-modified starch, cationized starch, amphoteric starch, etc.; additives such as polyvinyl alcohol, urea, defoaming agent, antioxidant, preservative, bactericide, etc. may be added. These may be used alone or in combination of two or more, and their content is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less, relative to 100 parts by weight of all the constituents.

[0036] The (meth)acrylamide polymer of the present invention can be obtained by appropriately adjusting the usage-amounts of the components (a1) to (a6).

[0037] The (meth)acrylamide polymer can be obtained by polymerizing the essential components (a1), (a2) and (a3), and, if necessary, the components (a4), (a5) and (a6) and the above-mentioned additives in a solvent in the presence of a polymerization initiator.

[0038] Examples of the polymerization method include a method using only a dropwise polymerization method, a method using only a simultaneous polymerization method (introducing a monomer mixed solution at once), and a method combining the simultaneous polymerization method and the dropwise polymerization method.

[0039] The dropwise polymerization method is a method of dropping a monomer mixture into a reaction system in which a solvent such as water has been previously introduced. As a method using only this polymerization method, for example, the following (1) to (3) can be cited. In addition, the dropwise addition can be continuous, or the dropwise addition can be stopped midway, and the dropwise addition can be restarted after a certain period of polymerization. (1) A method of adding dropwise a monomer mixed solution obtained by mixing all monomer components. (2) A method in which two or more monomer mixed solutions are prepared separately and then added dropwise simultaneously. (3) A method in which two or more monomer mixed solutions are prepared separately and then added dropwise in sequence.

[0040] In addition, examples of a method of combining the simultaneous polymerization method and the dropping polymerization method include the following (4) to (7). (4) A method in which each monomer mixed solution is polymerized simultaneously and then each polymer is mixed. (5) A method in which one or more monomer mixed solutions are polymerized simultaneously and after completion, the remaining monomer mixed solution is added dropwise. (6) A method of simultaneously polymerizing one or more monomer mixed solutions and then dropping the remaining monomer mixed solution to carry out polymerization. (7) A method in which more than one monomer mixture is added dropwise to carry out polymerization, and the remaining monomer mixture is added at once and then polymerized simultaneously.

[0041] As the solvent, water, organic solvents, etc. can be cited, and they can be used alone or in combination of two or more. As water, for example, tap water, pure water, ultrapure water, ion exchange water, industrial water, etc. can be cited. As the organic solvent, for example, alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, isobutanol, n-hexanol, n-octanol, ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and diacetone alcohol; ethers such as ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether can be cited. In addition, the content of the solvent is adjusted to preferably 5% to 50% by weight, more preferably 10% to 35% by weight, based on the polymerization concentration.

[0042] Examples of polymerization initiators include persulfates such as ammonium persulfate, potassium persulfate, and sodium persulfate; azo compounds such as 2,2'-azobis(2-amidinopropane) hydrochloride and 2,2'-azobis[2(2-imidazoline-2-yl)propane] hydrochloride; hydrogen peroxide, etc. These can be used alone or in combination of two or more. Among them, ammonium persulfate, potassium persulfate, and 2,2'-azobis(2-amidinopropane) hydrochloride are preferred in terms of allowing solution polymerization to proceed sufficiently. In addition, there is no particular limitation on the method for adding the polymerization initiator, and it can be appropriately selected to add once, add in portions, or add continuously. In addition, the content of the polymerization initiator is also not particularly limited, and is generally about 0.001 to 5 parts by weight, preferably about 0.01 to 1 part by weight, relative to 100 parts by weight of all the constituent components.

[0043] As polymerization conditions, for example, the reaction temperature is usually 50° C. to 100° C. (preferably 60° C. to 90° C.) and the reaction time is usually 1 hour to 10 hours (preferably 1 hour to 6 hours).

[0044] The physical properties of the obtained component (A) are, for example, that the weight average molecular weight is usually 1 to 10 million, preferably 1.5 to 7 million, in order to easily improve the paper strength effect of the paper strengthening agent. The "weight average molecular weight" herein refers to a value obtained by gel permeation chromatography (GPC).

[0045] The viscosity of component (A) is usually 1000 to 20000 mPa·s, preferably 3000 to 15000 mPa·s. The "viscosity" herein refers to a value measured by a B-type viscometer on a solution having a solid content concentration of 20 wt % and adjusted to 25° C. in advance.

[0046] Moreover, the component (A) may be used alone or in combination of two or more different components (A) produced separately.

[0047] In the present invention, a (meth)acrylamide polymer (A') not belonging to the component (A) (hereinafter referred to as the component (A')) may be used in combination. The component (A') is a polymer that does not contain the component (a2) and / or the component (a3) ​​in the constituent components.

[0048] The component (B) is a metal inorganic acid salt having a divalent or trivalent metal atom with an atomic weight of 30 to 80. When the component (B) is blended, it chemically interacts with the component (A), and the viscosity of the obtained paper strength enhancing agent is increased, thereby obtaining paper with excellent paper strength effect.

[0049] Examples of the metal atom include calcium, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, and gallium.

[0050] Examples of the inorganic acid salt include nitrates, hydrogen chloride salts (hydrochlorides), polyhydrochloride salts (polyhydrochlorides), sulfates, polysulfates, phosphates, polyphosphates, silicates (silicon salts), and polysilicates (polysilicon salts).

[0051] As component (B), any combination of the metal atom and the inorganic acid salt can be used freely. In addition, component (B) can also use a hydrate. In addition, these (B) components can be used alone or in combination of two or more. Among them, in terms of easy chemical interaction with component (A) and easy to make the paper strength effect excellent, titanium inorganic acid salts and iron inorganic acid salts are preferred, and more preferably one or more selected from the group consisting of titanium chloride, titanium sulfate, titanium phosphate, ferric nitrate, ferric chloride, polyferric chloride, ferric sulfate, polyferric sulfate, ferric phosphate, polyferric phosphate, ferric silicate and polyferric silicate.

[0052] The content of the component (B) is preferably 0.01 to 50 parts by weight, more preferably 0.05 to 35 parts by weight, and even more preferably 0.1 to 20 parts by weight, based on the weight of the non-volatile components, relative to 100 parts by weight of the component (A), in order to easily improve the paper strength effect of the paper strengthening agent. Here, the non-volatile components refer to the components remaining after removing volatile components such as water and organic solvents (the same applies hereinafter).

[0053] The paper strength enhancing agent of the present invention may be a mixture further comprising a water-soluble aluminum compound (C) (hereinafter referred to as component (C)). Examples thereof include aluminum sulfate, aluminum chloride, basic aluminum sulfate, basic aluminum chloride, aluminum silicate, polyaluminum chloride, polyaluminum hydroxide, and the like. In addition, component (C) may also be used in the form of a hydrate. These may be used alone or in combination of two or more. Among them, aluminum sulfate, aluminum chloride, and polyaluminum chloride are preferred in terms of easy availability.

[0054] The content of the component (C) is preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and even more preferably 2 parts by weight or less, based on 100 parts by weight of the component (A), in terms of the nonvolatile content.

[0055] The paper strength enhancer of the present invention may further include inorganic acid salts such as sodium sulfate, potassium sulfate, ammonium sulfate, etc. that do not belong to component (B); starches such as oxidized starch, phosphated starch, urea-phosphated starch, etherified starch, cross-linked starch, APS-modified starch, enzyme-modified starch, cationized starch, amphoteric starch, etc.; additives such as polyvinyl alcohol, urea, defoaming agent, antioxidant, preservative, bactericide, etc.

[0056] The paper strength enhancer of the present invention can be obtained in the form of a mixture by stirring or mixing the (A) component and the (B) component, the (A') component as required, the (C) component and the additives at room temperature. In addition, when preparing the mixture, the mixture can also be heated or cooled appropriately. As a mixing method, the (A) component and the (B) component, the (A') component and the (C) component as required can be mixed in the state of stock solution, or one or more selected from the (A) component and the (B) component, the (A') component and the (C) component as required can be diluted with water in advance and then mixed. In addition, after mixing, water can be further added for dilution. In addition, when two or more different (meth)acrylamide polymers are used as the (A) component, they can be mixed with the components at one time, or the (meth)acrylamide polymers used in combination can be mixed with each other in advance (and can also be mixed with the (A') component as required), and then the remaining components can be added for mixing.

[0057] Examples of water include tap water, pure water, ultrapure water, ion exchange water, and industrial water. In addition, the nonvolatile concentration of each component after dilution is preferably adjusted to the following from the perspective of obtaining a paper strengthening agent in which each component is well dispersed and has an appropriate viscosity: (A) component: preferably 0.1 wt% to 10 wt%, more preferably 0.3 wt% to 5 wt%; (B) component: preferably 0.1 wt% to 10 wt%, more preferably 0.3 wt% to 5 wt%; (C) Component: preferably 0.1 to 10% by weight, more preferably 0.3 to 5% by weight.

[0058] As for the physical properties of the obtained paper strengthening agent, in order to obtain a paper strengthening agent in which each component is well dispersed and has an appropriate viscosity and a high paper strengthening effect, the viscosity of the mixture at a temperature of 25° C. when it is prepared as an aqueous solution of pH=6 containing 1% by weight of the component (A) in terms of non-volatile content concentration is preferably 5 mPa·s or more and 5000 mPa·s or less, more preferably 10 mPa·s or more and 3000 mPa·s or less, and even more preferably 15 mPa·s or more and 2000 mPa·s or less. The viscosity here is a value measured by a B-type viscometer.

[0059] In order to adjust the pH when measuring the viscosity, for example, the following can be used as a pH adjuster: an inorganic acid such as hydrochloric acid, sulfuric acid, phosphoric acid; an inorganic base such as sodium hydroxide, potassium hydroxide, calcium hydroxide, etc.

[0060] The paper of the present invention includes the paper strengthening agent. As a method for producing the paper of the present invention, for example, the paper strengthening agent is added to the raw material pulp slurry (hereinafter also referred to as internal addition); the paper strengthening agent is sprayed (injected) onto the surface of wet paper; or the paper strengthening agent is applied to the surface of base paper, etc. In addition, the paper strengthening agent can be used directly at the above non-volatile component concentration, or it can be further diluted with water to adjust the non-volatile component concentration to 0.1% by weight to 10% by weight.

[0061] When the paper strength enhancer is added to the raw material pulp slurry, the paper strength enhancer is added to the pulp slurry and papermaking is performed. The amount of the paper strength enhancer used (calculated as the non-volatile component of the (A) component) is about 0.01% by weight to 4% by weight relative to the dry weight of the pulp. In addition, as the types of pulp, for example, chemical pulps such as hardwood pulp (LBKP) and softwood pulp (NBKP); mechanical pulps such as groundwood pulp (GP), refined wood pulp (RGP), and thermomechanical pulp (TMP); waste paper pulp such as waste corrugated paper, etc. can be listed. In addition, when adding paper strength enhancers, in addition to these, pH adjusters such as aluminum sulfate, sulfuric acid or sodium hydroxide; papermaking chemicals such as sizing agents or wetting paper strength agents; and fillers such as talc, clay, kaolin, titanium dioxide, and calcium carbonate may also be added as fixatives.

[0062] When spraying (injecting) onto the surface of wet paper, the paper strength agent is sprayed onto the surface of one or more layers of wet paper before lamination before lamination. The paper strength agent is diluted to a non-volatile component concentration of about 0.1% by weight to 7% by weight before use. In addition, the viscosity after dilution is about 2mPa·s to 50mPa·s (non-volatile component concentration 1.0% by weight, 25°C) at a temperature of 25°C. The amount of the paper strength agent used (in terms of non-volatile component conversion) is usually 0.05% by weight to 10% by weight relative to the total pulp (non-volatile component weight).

[0063] When applied to the surface of base paper, the paper strength enhancer is applied to the surface of base paper by various known means. Here, the paper strength enhancer applied to the surface of the base paper is referred to as a "coating liquid". The viscosity of the coating liquid is usually 1 mPa·s to 50 mPa·s at a temperature of 50°C. As the type of base paper, uncoated paper made of wood cellulose fiber can be used, and as the coating means, for example, rod coater, knife coater, air knife coater, calender, gate roll coater, blade coater, double roll size press or metering rod, etc. In addition, the coating amount of the coating liquid (calculated as non-volatile components) is usually 0.001 g / m 2 ~2g / m 2 About 0.005 g / m 2 ~1g / m 2 about.

[0064] The paper of the present invention can be used in various products, for example, coated base paper, newspaper paper, liner paper, core paper, paper tube, printing and writing paper, form paper, PPC paper, paper cup base paper, inkjet paper, thermal paper, etc. Example

[0065] Hereinafter, the present invention will be described with reference to Examples, but the present invention is not limited thereto. In addition, "parts" and "%" in Examples and Comparative Examples are by weight unless otherwise specified.

[0066] The following compounds are shown by abbreviations. AM: Acrylamide DM: N,N-dimethylaminoethyl methacrylate DML: N,N-dimethylaminoethyl methacrylate benzyl chloride BQ: N,N-dimethylaminoethyl acrylate benzyl chloride APDM: dimethylaminopropyl acrylamide IA: itaconic acid AA: Acrylic acid AGA: 2-Acrylamido-N-glycolic acid SMAS: Sodium Methyl Allyl Sulfonate DMAA: N,N-dimethylacrylamide MBAA: N,N'-Methylenebisacrylamide APS: Ammonium Persulfate

[0067] Production Example 1 276.5 parts of ion exchange water were placed in a reaction apparatus equipped with a stirrer, a thermometer, a reflux cooling tube, a nitrogen inlet tube and three dropping funnels, and nitrogen was introduced to remove oxygen in the reaction system, and then heated to 90° C. Into the dropping funnel (1), 70.5 parts (21.3 mol%) of AM, 58.7 parts (8.0 mol%) of DM, 2.4 parts (0.40 mol%) of IA, 1.11 parts (0.15 mol%) of SMAS, 28.7 parts (0.05 mol%) of 62.5% sulfuric acid, 0.23 parts (0.05 mol%) of DMAA, 0.36 parts (0.05 mol%) of MBAA and 218.9 parts of ion exchange water were placed, and the pH was adjusted to about 3.0 with sulfuric acid (monomer mixture (I)). In addition, 203.9 parts (61.4 mol%) of AM, 58.7 parts (8.0 mol%) of DM, 2.4 parts (0.40 mol%) of IA, 1.11 parts (0.15 mol%) of SMAS, 0.23 parts (0.05 mol%) of DMAA, 0.36 parts (0.05 mol%) of MBAA and 466.6 parts of ion exchange water were added to the dropping funnel (2), and the pH was adjusted to about 3.0 with sulfuric acid (monomer mixture (II)). 0.6 parts of APS and 180 parts of ion exchange water were added to the dropping funnel (3). Then, the catalyst was added dropwise to the system through the dropping funnel (3) over about 3 hours. At the same time, the monomer mixture (I) and the monomer mixture (II) in the dropping funnel (1) and the dropping funnel (2) were added dropwise in this order at a constant flow rate over about 3 hours. After the dropwise addition, 0.4 parts of APS and 10 parts of ion exchange water were added and kept warm for 1 hour, and 580 parts of ion exchange water were added to obtain an aqueous solution of component (A-1) having a non-volatile content concentration of 20.0%. In addition, the molar ratios of all monomer components are shown in Table 1, and the molar ratios of the monomer components added to each monomer mixed solution are shown in Table 2.

[0068] Production Example 2 to Production Example 18 With the compositions shown in Table 1 and Table 2, synthesis was carried out in the same manner as in Production Example 1 to obtain aqueous solutions of paper strengthening agents having a nonvolatile content concentration of 20.0%.

[0069] <Viscosity> The viscosity of the component (A) in each Production Example adjusted to 25° C. was measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.).

[0070] <Weight Average Molecular Weight> The weight average molecular weight of the component (A) was measured by gel permeation chromatography (GPC) under the following measurement conditions. Column: One PWXL and two GMPWXL protective columns manufactured by Tosoh Corporation Eluent: Phosphate buffer (0.05 mol / L phosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) + 0.13 mol / L sodium dihydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) aqueous solution, pH about 2.5) Flow rate: 0.8ml / min Temperature: 40℃ RI detector: Shodex RI-101 manufactured by Showa Denko K.K. MALS detector: DAWN HELEOS-II manufactured by WYATT Measurement sample: The sample was diluted with the eluent so that the nonvolatile content of the component (A) became 0.1%, and then measured.

[0071] [Table 1]

[0072] [Table 2]

[0073] Ion exchanged water was added so that the nonvolatile content concentration of each of the components (A) of each manufacturing example and the components (B) and (C) described in Table 2 was 2%. In Example 6, an aqueous solution was used in which ion exchanged water was added so that the nonvolatile content concentration of each of the components (A-1) and (B-1) was 4%.

[0074] Example 1 500 parts of a 2% aqueous solution of the component (A-1) (10.0 parts of non-volatile components), 150 parts of a 2% aqueous solution of polyferric sulfate (trade name: "Polytet", manufactured by Nippon Iron & Steel Co., Ltd.) (3.0 parts of non-volatile components) and 350 parts of ion-exchanged water were added and mixed at room temperature for 30 minutes to obtain a paper strengthening agent.

[0075] Examples 2 to 5, Examples 7 to 36, Comparative Examples 1 to 4 The same method as in Example 1 was carried out by changing the ingredients and usage amounts shown in Table 2 to obtain paper strengthening agents.

[0076] Example 6 250 parts of a 4% aqueous solution of the component (A-1) (10.0 parts of non-volatile components), 500 parts of a 4% aqueous solution of polyferric sulfate (trade name: "Polytet", manufactured by Nippon Iron & Steel Co., Ltd.) (20.0 parts of non-volatile components) and 250 parts of ion-exchanged water were added and mixed at room temperature for 30 minutes to obtain a paper strengthening agent.

[0077] <Viscosity> After adding sodium hydroxide aqueous solution (non-volatile content concentration: 10%, 5%, 1%) to each paper strengthening agent to adjust the pH to 6, the temperature was adjusted to 25°C, and the viscosity was measured using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd.). The results are shown in Table 3.

[0078] (Papermaking Evaluation 1: Evaluation based on differences in paper strength enhancing agents) Waste corrugated paper was beaten with a Niagara beater, and calcium chloride was added to the pulp slurry adjusted to a Canadian Standard Freeness (CSF) of 350 ml to adjust the conductivity to 2.0 mS / cm. Aluminum sulfate was added to the slurry liquid at a rate of 1.0% (non-volatile component) relative to the weight of the non-volatile components of the pulp slurry. After stirring for 30 seconds, each of the paper strength enhancers was added at a rate of 1.0% relative to the weight of the non-volatile components of the pulp slurry as the non-volatile components of component (A). The pH of each pulp slurry was adjusted to 6.5 for evaluation. Dewatering was performed with a TAPPI sheeter and heated at 5 kg / cm 2 Press for 2 minutes and make paper with a basis weight of 150g / m 2 Then, the paper was dried at 105°C for 4 minutes using a rotary dryer and humidified at 23°C and 50% for 24 hours to obtain finished paper 1. The texture, specific bursting strength, specific tensile strength and specific compressive strength of the finished paper 1 were measured using the following method. The results are shown in Table 3.

[0079] <Electrical conductivity> The measurement was performed using pH / COND METER D-54 (manufactured by Horiba, Ltd.). <Texture (Texture Variation Coefficient)> The transmitted light (brightness) from the paper obtained above was input into a commercially available measuring instrument (trade name "Personal Image Processing System Hyper-700", manufactured by OBS), and the brightness distribution was statistically analyzed. The value obtained was used as the texture variation coefficient. The smaller the value of the texture variation coefficient, the better the texture. <Specific Bursting Strength> The paper obtained above was used to measure the specific bursting strength (kPa·m 2 / g). <Specific tensile strength> The specific tensile strength (N·m / g) was measured in accordance with JIS P 8113 using the paper obtained above. <Specific compressive strength> The paper obtained above was used to measure the specific compressive strength (N·m 2 / g).

[0080] [Table 3]

[0081] The symbols in Table 3 represent the following components. <(A)Component> A-1 to A-18: Acrylamide polymers of Production Examples 1 to 18 (compounded in the same order) <(B) Component> B-1: Polyferric sulfate (trade name: "Polyte", manufactured by Nippon Iron & Steel Co., Ltd.) ·B-2: Ferric (III) chloride (trade name: "Ferric chloride liquid (iron chloride second iron liquid)", manufactured by Taiki Chemical Industry Co., Ltd.) · B-3: Polysilicate iron (trade name: "PSI-025", manufactured by Naoji Chemicals (Naoji Pharmaceuticals Co., Ltd.) · B-4: Titanium (IV) sulfate (n-hydrate) (manufactured by Kishida Chemical Co., Ltd.) <(C) Ingredients> ·C-1: Aluminum sulfate (manufactured by Asada Chemical Co., Ltd., liquid aluminum sulfate) ·C-2: Polyaluminium chloride (manufactured by Asada Chemical Co., Ltd.) <(D) Component> ·D-1: Zirconium sulfate (tetrahydrate) (manufactured by Kishida Chemical Co., Ltd.)

[0082] (Papermaking Evaluation 2: Evaluation based on the order of adding chemicals) Evaluation Example 1, Comparative Evaluation Examples 1 to 3 Waste corrugated paper was beaten with a Niagara pulper, and calcium chloride was added to the pulp slurry adjusted to a Canadian standard freeness (CSF) of 350 ml to adjust the conductivity to 2.0 mS / cm. Aluminum sulfate was added to the slurry liquid at a weight of 1.0% (non-volatile component) relative to the non-volatile component of the pulp slurry, and the components listed in Table 4 were added and stirred 15 seconds, 30 seconds, and 45 seconds after this time point. The pH of each pulp slurry was adjusted to 6.5 for evaluation. Dewatering was performed with a TAPPI sheeter and heated at 5 kg / cm 2 Press for 2 minutes and make paper with a basis weight of 150g / m 2 Then, the paper was dried at 105°C for 4 minutes using a rotary dryer and conditioned at 23°C and 50% humidity for 24 hours to obtain finished paper 2. The texture, specific bursting strength, specific tensile strength and specific compressive strength of the finished paper 2 were measured using the same method as above. The results are shown in Table 4.

[0083] [Table 4] *1: Indicated by the amount of component (A-1) used as non-volatile matter.

[0084] The symbols shown in Table 4 represent the following components. Example 1: Paper strength enhancer of Example 1 A-1: Acrylamide polymer of Production Example 1 B-1: Polyferric sulfate (trade name: "Polyte", manufactured by Nippon Iron & Steel Co., Ltd.)

[0085] As can be seen from Table 4, the paper strengthening agent (Example 1) obtained by mixing components (A) and (B) exhibits a superior paper strengthening effect compared to the case where components (A) and (B) are added separately to the pulp slurry.

Claims

1. A paper strength enhancer, wherein: The paper strength enhancing agent comprises a mixture of a (meth)acrylamide polymer (A) and a metal inorganic acid salt (B), wherein the (meth)acrylamide polymer (A) comprises (meth)acrylamide (a1), a polymerizable monomer having an amino group (a2) and a polymerizable monomer having a carboxyl group (a3) ​​as essential components, and the metal inorganic acid salt (B) comprises a divalent or trivalent metal atom having an atomic weight of 30 to 80.

2. The paper strengthening agent according to claim 1, wherein: The viscosity of the mixture at a temperature of 25° C. when the mixture is prepared as an aqueous solution of pH=6 containing 1% by weight of the component (A) as a nonvolatile content is 5 mPa·s or more and 5000 mPa·s or less.

3. The paper strengthening agent according to claim 1 or 2, wherein: The above-mentioned constituent components further include a polymerizable monomer (a4) having a sulfonic acid group and / or a polymerizable monomer (a5) having a crosslinkable group.

4. The paper strengthening agent according to claim 1 or 2, wherein: The component (B) is at least one selected from the group consisting of titanium chloride, titanium sulfate, titanium phosphate, ferric nitrate, ferric chloride, polyferric chloride, ferric sulfate, polyferric sulfate, ferric phosphate, polyferric phosphate, ferric silicate and polyferric silicate.

5. The paper strengthening agent according to claim 1 or 2, wherein: The mixture further comprises a water-soluble aluminum compound (C).

6. A paper comprising the paper strengthening agent according to claim 1 or 2.

Citation Information

Patent Citations

  • Production of paper

    JP1996226092A

  • Process for papermaking

    JP2001011787A

  • Polyacrylamide-based internal paper-strengthening agent and method for producing paper

    JP2012251252A